Exploring the Contributions of Women in the History of Philosophy, Science, and Literature, Throughout Time - Harry, Chelsea C.; Vlahakis, George N. (Springer, 2023)
This book explores contributions by some of the most influential women in the history of philosophy, science, and literature
Keywords: dept.phi